An enhanced deadbeat predictive current control of SPMSM with linear disturbance observer - Yuan, Xin (2023)
Deadbeat predictive current control (DPCC) with a linear disturbance observer (LDO) in the surface-mounted permanent magnet synchronous machine (SPMSM) has been widely applied in many applications due to better dynamic response performance and easy implementation. However, the evaluated lumped disturbances caused by current measurement noises, inverter nonlinearity, abrupt reference current, and initial inductance parameter mismatch can restrain the high-performance development. In order to handle this issue, an enhanced DPCC with LDO is proposed in this article, where a modified DPCC with the LDO model and the noninvasive inductance and inverter disturbance observer are developed. In this case, the initial inductance parameter mismatch and high-frequency disturbances effect on the DPCC with LDO is reduced, while the current measurement noises' suppression is enhanced by the proposed LDO. The theoretical analysis has shown that the proposed DPCC with LDO has a better performance than the conventional DPCC with LDO. Also, the superiority of the proposed DPCC with LDO has been validated by an SPMSM drive test rig.